Performance Improvement of the Implementation of Concrete Structures in the Construction Sector In Iraq Using The Modern Management Technique “Six Sigma” (Journal of Engineering, 2015)
The reality of the field of construction projects in Iraq refers to needing for the development of performance in order to improve quality and reduce defects and errors and to control the time and cost, so there is needing for the application of effective methods in this area, one of the methods that can be applied in this area is the manner of Six Sigma. This research aims to enhance the performance and quality improvement for the construction projects by improving performance in the work of the implementation of the concrete structure depending on the Six Sigma methodology, and for the purpose of achieving the aim of the research, the researcher firstly depends on the theoretical study that include the concepts of quality and the Six Sigma methodology as a system aims to reduce defects and improve the quality and secondly on the field study carried out by the researcher through conducting the open questionnaire that include interviews conducted by the researcher with a slice of engineers experienced in the implementation of construction projects that leads to design closed questionnaire included the major axes of  the research and distributed on a selected sample of engineers with expertise in this area. The researcher applying the (DMAIC) methodology is one of the methods adopted for the application of Six Sigma on the case study (the project of structures laboratory at University of Baghdad) for the purpose of identifying the most important defects that may appear in the implementation of the concrete structure and assess the quality of implementation of the concrete structure and then analyzing the causes of these defects and propose procedures to enhance the performance and quality improvement depending on the field survey was conducted. The most important research conclusions are sigma level for the case study is 2.35 and the number of defects per million opportunities is 211905 and this Sigma level is very small which indicates the low level of quality for the case study.